Advances in insect physiology. - Evans, P. D. (Advances in insect physiology, 1994)
Insect physiology is currently undergoing a revolution with the increased application of molecular biological techniques to investigate the molecular mechanisms underlying the physiological responses to insect cells. Advances in Insect Physiology has instituted a commitment to the publication of high quality reviews on molecular biology and molecular genetics in areas where they provide an increased understanding of physiological processes in insects. Volume 25 contains increased coverage on the molecular biology of insect physiology.